Oleic Acid Esterification Catalyzed By Zeolite Y-Model of the Biomass Conversion - Gomes, Glaucio José (2019)
Residual oils and fats are promising renewable sources for the production of liquid fuels and the synthesis of various chemicals with significant life cycle and large-scale economic advantages over other biomass sources. Thus, oleic acid esterification was investigated on zeolites type FAU and sulfuric acid by kinetic, spectroscopic assessments and theoretical calculations using a hybrid ONIOM scheme. In the catalytic tests, the solid catalyst with the highest Si/Al (H-Y-80) ratio showed the highest catalytic activity for esterification (92% conversion) as compared to H-Y-5.2 (66% conversion), Na-Y (15% conversion) and homogeneous acid catalysis (89% conversion). The catalytic activity between different acid catalysts is discussed. It was observed that the acidity of the active sites and the hydrophobicity resulting from the Si/Al molar ratio influence the esterification conversion. Theoretical calcultations predicts that the voluminous confined space of the FAU zeolite perfectly accommodates the oleic acid molecule in the adsorption step (Eads= -25.5 kJ mol-1) and the van der Waals interactions of the zeolite walls with the aliphatic chain help to accommodate the bulky molecule between the supercages. Experimental and theoretical results confirm that H-Y-80 zeolite applied in the esterification reaction can be an efficient catalyst in processes involving conversion of unsaturated fatty acids.